Increased Risk of Malaria During the First Year of Life in Small-for-Gestational-Age Infants: A Longitudinal Study in Benin. (7th December 2018) - Agbota, Gino; Accrombessi, Manfred; Cottrell, Gilles; Martin-Prével, Yves; Milet, Jacqueline; Ouédraogo, Smaïla; Courtin, David; Massougbodji, Achille; Garcia, André; Cot, Michel; Briand, Valérie
Abstract : Using a logistic mixed regression model, we assessed the effect of SGA on risk of malaria morbidity from 0 to 12 months. SGA was associated with a 2-times higher risk of malaria infection and clinical malaria after age 6 months. Abstract: Background: According to the Developmental Origins of Health and Diseases paradigm, the fetal period is highly vulnerable and may have profound effects on later health. Few studies assessed the effect of small-for-gestational age (SGA), a proxy for fetal growth impairment, on risk of malaria during infancy in Africa. Methods: We used data from a cohort of 398 mother-child pairs, followed from early pregnancy to age 1 year in Benin. Malaria was actively and passively screened using thick blood smear. We assessed the effect of SGA on risk of malaria infection and clinical malaria from birth to 12 months, after stratifying on the infant's age using a logistic mixed regression model. Results: After adjustment for potential confounding factors and infant's exposure to mosquitoes, SGA was associated with a 2-times higher risk of malaria infection (adjusted odds ratio [aOR] = 2.16; 95% confidence interval [CI], 1.04–4.51; P = .039) and clinical malaria (aOR = 2.33; 95% CI, 1.09–4.98; P = .030) after age 6 months. Conclusion: Results suggest higher risk of malaria during the second semester of life in SGA infants, and argue for better follow-up of these infants after birth, as currently for preterm babies.